Basic & clinical pharmacology 2026-02-15T16:22:58+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Katzung, Bertram G.; Masters, Susan B.; Trevor, Anthony J. (McGraw-Hill Medical ; McGraw-Hill [distributor], 2009)

(untitled)
Looks at the essential conepts in the science of pharmacology and its application to clinical practice